OP0186 DISTINCT PERIPHERAL IMMUNOPHENOTYPING UNDERLINES HISTOPATHOLOGICAL FEATURES IN PATIENTS WITH LUPUS NEPHRITIS IN A LARGE MULTI-CENTER COHORT - Horisberger, A.; Griffith, A.; Keegan, J.; Howard, K.; Pulford, J.; Murzin, E.; Hancock, B.; Ghosh, T.; Sasaki, T.; Fava, A.; Gutierrez Arcelus, M.; Eisenhaure, T.; et al. (Annals of the rheumatic diseases, 2023)
BackgroundLupus nephritis (LN) is a common and severe complication of systemic lupus erythematosus (SLE) requiring renal biopsy to guide treatment decisions. Despite standard-of-care therapy, a third of patients with LN class III, IV, or V show a progressive decline in kidney function, including those with improved proteinuria. Defining LN heterogeneity using a non-invasive approach is a pressing need to improve treatment.ObjectivesTo determine circulating immune cell phenotypes characteristic of LN histology.MethodsMass cytometry using four 48-marker panels were applied to characterize peripheral blood mononuclear cells (PBMC) from 140 patients with biopsy-proven class III, IV, or V LN and 40 healthy controls included in the Accelerated Medicine Partnership RA/SLE Network Phase II study. After filtering for quality control and correcting for batch effects, we projected cells in a reduced dimensional space and identified cell neighborhoods and clusters using an unsupervised approach. We implemented covarying neighborhood analysis (CNA) to identify cell populations associated with clinical features.ResultsCompared to controls, LN patients displayed marked enrichment of cell neighborhoods that expressed interferon (IFN)-induced proteins including MX1 (p.adj < 0.001) and Siglec1 (p.adj < 0.001), reflecting a simple, cytometric detection of an IFN signature. Detailed immune cell subsetting using the B cell- (Figure 1A), T cell-, myeloid cell-, and NK cell-focused panels identified several alterations in LN patients compared to controls, including increased CD27-IgD-(DN) CD11c+Tbet+ B cells (OR 1.6, 95%CI 1.3-2.2, p.adj < 0.001) and T peripheral helper cells (OR 1.8, 95%CI 1.3-2.8, p.adj = 0.002), and decreased plasmacytoid dendritic cells (OR 0.6, 95%CI 0.4-0.8, p.adj < 0.001), adjusting for age, sex, ethnicity and race. LN patients with minimal immunosuppression (IS, n=14) displayed similar results. Comparing patients with proliferative LN (class III or IV +/- V, n=94) versus membranous LN (class V, n=46), we observed the most significant alterations within B cells, with enrichment of a naive B cell population characterized as CD23- and CD21dim (Figure 1B,C). The phenotype of this enriched naive B cell population was distinct from transitional and CD11c+ ‘activated naive’ cells (Figure 1D). This B cell population was also associated with increased histologic NIH activity score (Figure 1B,C) even after adjusting for IS, and with positive anti-dsDNA antibody (p = 0.02). To further understand the LN heterogeneity, we clustered LN patients and controls based on proportions of all PBMC subsets using k-means clustering and projected subjects in a UMAP space. We identified two prominent clusters: cluster 1 included only LN patients, and cluster 2 included all controls and 26 LN patients. LN patients in cluster 2 (Control-like) had significantly lower clinical extrarenal activity (coef -1.1, 95%CI -2.1--0.1, p.adj = 0.03) and IFN-induced protein expression (coef -28.0, 95%CI -36.6—19.4, p.adj < 0.001), adjusting for IS. In addition, these patients had significantly higher histologic chronicity (coef 2.39, 95%CI 1.24-3.53, p.adj < 0.001). In line with these findings, we confirmed by CNA the association of increased histologic chronicity with fewer MX1+ or Siglec1+ IFN-responsive cells, adjusting for IS (p.adj = 0.002, FDR < 10%).ConclusionIn addition to profoundly impaired circulating immunophenotype observed in LN patients, we identified a difference in naive B cell states in patients with proliferative LN compared to membranous LN. Based on circulating immunophenotype, we identified a subset of SLE patients with low extrarenal activity and increased histologic evidence of chronic kidney damage. These results nominate potential non-invasive biomarkers associated with LN heterogeneity and highlight altered naive B cell activation in proliferative LN.Figure 1.REFERENCES:NIL.Acknowledgements:NIL.Disclosure of InterestsNone Declared.